Effectiveness of Counseling Using Puzzle Games and Lectures on Index Debris and Index Plaque in Class IV and V Students at Muhammadiyah Meruyung Primary School, Depok - Mardiati, Erni; Nurilawaty, Vitri; Noviani, Nita; Wiradona, Irmanita (Jurnal Kesehatan Gigi, 2024)
Health education aims to raise awareness and encourage people to adopt healthy practices, especially in dental health for elementary school children. Dental health is crucial as it affects overall health and requires early intervention. Elementary school children are particularly at risk for dental issues. A screening at SD Muhammadiyah Meruyung Depok showed an average debris index of 2.7, indicating poor dental hygiene among students in grades IV and V. The aim of this research was to determine the effectiveness of index debris and index plaque values before and after being given counseling using puzzle games with lectures. This type of research is analytical, the method used is Quasy Experimental pre and post test design with control group with a sample size of 66 respondents. The sampling technique used purposive sampling technique and statistical tests using the Wilcoxon and Mann Whitney tests were used to determine the effectiveness of the research results. The results of this study show that puzzle games are more effective than lectures. The average change value of puzzle games was higher than lectures for both index debris and index plaque. The statistical test results obtained a significant value 0.05. The conclusion from the research results is that puzzle games are more effective in reducing index debris and index plaque in class IV and V students at SD Muhammadiyah Meruyung Depok